FEN VE TEKNOLOJİ ÖĞRETMEN ADAYLARININ BİLGİ OKURYAZARLIĞI VE MEDYA OKURYAZARLIĞI DÜZEYLERİNİN İNCELENMESİ. - GÜVEN, İlknur (Electronic Turkish Studies)
With the development of technology information sources are diversified and the concept of information literacy and media literacy has gained significance. It is important for the teachers those have the duty of teaching information to be information literate and media literate because new generations will be raised by them. The aim of the study was to determine the level of information literacy and media literacy of the science teacher candidates those were 1 grade and 4 grade students of a science teaching program of a university in Istanbul, Turkey. In addition to this it was aimed to determine the relationship between information literacy and media literacy of the science teacher candidates. The research is a descriptive research designed as a relational survey method. In order to determine the level of information literacy of the candidate teachers "information literacy scale" was used which was a five-point likert-type scale with 35 items. In order to determine the level of media literacy of the candidate teachers five-point likert-type "media literacy scale" was used that was consisting of a total of 17 items. The data obtained from the study were analyzed by SPSS software package. Analyses of the application of the scales to the 1 grade and 4th grade students a significant correlation was found between the information literacy and media literacy levels of the students. While any significant difference was not found between 1 grade and 4th grade teacher candidates' information literacy levels, a significant difference was found between the level of media literacy levels of these groups.